Glycans and glycan binding proteins in immune regulation: A concise introduction to glycobiology for the allergist - Schnaar, Ronald L. (J Allergy Clin Immunol, 2015)
Cells are endowed with a rich surface coat of glycans carried as glycoproteins and glycolipids on the outer leaflet of their plasma membranes and constituting a major molecular interface between cells and their environment. Each cell’s glycome, the sum of its diverse glycan structures, comprises a distinct cellular signature that is defined by the expression levels of the enzymes responsible for glycan biosynthesis. This signature can be read by complementary glycan binding proteins that translate glycan recognition into function. Nowhere is this more evident than in the immune system, where glycans and glycan binding proteins are integral to pathogen recognition and the control of inflammatory responses. Glycobiology – the study of glycan structures and their functions – is increasingly providing insights into immune regulatory mechanisms and thereby providing opportunities for therapeutic intervention. To promote wider appreciation of this rapidly expanding area of research, this review briefly examines the makeup of the human glycome, the glycan binding proteins that translate glycan recognition into function, and provides examples of glycan recognition events that are responsible for immune system regulation.